Shaping Pedagogy Through Practice: Reflections on the Spanish Program in International Studies at UTS - Elena Sheldon (PORTAL: Journal of Multidisciplinary International Studies)
As the University of Technology Sydney (UTS) celebrates 30 years of the Bachelor of International Studies (BIS), I reflect on my journey leading the Spanish program.  This reflection examines the implementation of genre-based pedagogy inspired by Systemic Functional Linguistics (SFL), which has been instrumental in bridging gaps in traditional teaching methods and fostering academic literacy. Drawing on collaborations with Spanish universities and integrating cutting-edge resources, I have witnessed the transformative impact of these initiatives on students' preparation for in-country study and their ability to navigate academic and cultural challenges. These experiences have also shaped my teaching philosophy, highlighting the value of research-informed practices in enhancing language proficiency and intercultural competence.